El control concreto de constitucionalidad, su incidencia y efectos en la reparación de decisiones adoptadas por la justicia ordinaria. - Muyolema Masaquiza, Tatiana Maribel (2023)
The present research project called "The concrete control of constitutionality, and its incidence and effects in the repair of decisions adopted by the ordinary justice", focuses the cornerstone of the investigation on the role and actions of the judges in direct relation to what is contemplated in the Constitution of the Republic of Ecuador, in relation to the system of control of constitutionality. Taking into account the legal regulations, the doctrine and the scope and nature of the principles according to what the Constitutional Court of Ecuador interprets through its mandatory sentences. Break down the jurisdiction and competence of the judges of the Constitutional Court, with a transversal approach in which the concrete control (concentrated) and the diffuse control of constitutionality, the discretion of the ordinary judges and the events that can derive from the interpretation will be discussed. directly from the judges aquo of the constitutional text, without contemplating the provisions of article 428 ibídem, or if the terms contemplated in the Organic Law of Jurisdictional Guarantees and Constitutional Control are not fulfilled due to the procedural burden of the constitutional judges. The effects that may be caused by the discretion in the resolutions of the judges of first instance, and the non-observance of an express mandate and jurisprudence, which would result in a violation of the principles of legal certainty of the State, effective judicial protection and due process. In the same way, in application of article 417 and 425 of the Constitution, what is developed by the Inter-American Court of Human Rights in cases similar to those studied in this investigation will be taken as jurisprudential references, in order to determine the responsibility of the Ecuadorian State against to cases in which the American Convention on Human Rights is violated in the application of diffuse control of constitutionality or application of the discretion of the judge of first instance.